Shock Therapy for Clean Innovation: Within-Firm Reallocation of R&D Investments - Esther Ann Bøler; Katinka Holtsmark; Karen Helene Ulltveit-Moe (CESifo GmbH, 2024)
We analyze how a major negative shock to the producers of fossil fuels may lead to a shift from dirty to clean R&D along the supply chain. First, we develop a theoretical framework of directed technical change, showing that adjustment costs in R&D activity can lead fossil energy sector suppliers to shift their R&D activity towards clean innovation more than other firms, as a consequence of a negative oil price shock. Second, we investigate the impact of a major drop in the oil price in 2014 on clean R&D. Relying on rich firm level trade data, we propose a novel method of identifying firms' exposure to the price shock. We find that more exposed firms increased their clean R&D investments more than less exposed firms. Our findings contribute to the understanding of the drivers of clean technological change, which is vital to assess the effectiveness of different climate policy measures, including carbon pricing.
Keywords: D25; F18; O31; Q55; Q58; 330; clean innovation; supply chains; carbon pricing